Circulating cellular adhesion molecules and risk of diabetes: the Multi‐Ethnic Study of Atherosclerosis (MESA). Issue 7 (25th March 2016) - Pankow, J. S.; Decker, P. A.; Berardi, C.; Hanson, N. Q.; Sale, M.; Tang, W.; Kanaya, A. M.; Larson, N. B.; Tsai, M. Y.; Wassel, C. L.; Bielinski, S. J.
Abstract: Aims: To test the hypothesis that soluble cellular adhesion molecules would be positively and independently associated with risk of diabetes. Methods: Soluble levels of six cellular adhesion molecules (ICAM‐1, E‐selectin, VCAM‐1, E‐cadherin, L‐selectin and P‐selectin) were measured in participants in the Multi‐Ethnic Study of Atherosclerosis, a prospective cohort study. Participants were then followed for up to 10 years to ascertain incident diabetes. Results: Sample sizes ranged from 826 to 2185. After adjusting for age, sex, race/ethnicity, BMI and fasting glucose or HbA1c, four cellular adhesion molecules (ICAM‐1, E‐selectin, VCAM‐1 and E‐cadherin) were positively associated with incident diabetes and there was a statistically significant trend across quartiles. Comparing the incidence of diabetes in the highest and lowest quartiles of each cellular adhesion molecule, the magnitude of association was largest for E‐selectin (hazard ratio 2.49; 95% CI 1.26–4.93) and ICAM‐1 (hazard ratio 1.76; 95% CI 1.22–2.55) in fully adjusted models. Tests of effect modification by racial/ethnic group and sex were not statistically significant for any of the cellular adhesion molecules ( P > 0.05). Conclusions: The finding of significant associations between multiple cellular adhesion molecules and incident diabetes may lend further support to the hypothesis that microvascular endothelial dysfunction contributes to risk of diabetes. What's new?: Most prospective studies of cellular adhesion molecules and incident diabetes have been limited to a few cellular adhesion molecules and have predominantly been conducted in populations of European descent. We tested the associations between six different cellular adhesion molecules and risk of diabetes in a diverse, population‐based sample. Significant associations between multiple cellular adhesion molecules and incident diabetes may indicate an important role of microvascular endothelial dysfunction in the pathophysiology of Type 2 diabetes.